Characteristics of the neurohormonal control of static muscle activity in children - Sitdikova A.A. ,; Dikopolskaya N.B. ,; Bilalova G.A. ,; Shaykhelislamova M.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to investigate the reaction of the sympathetic-adrenal system to localized static strain in children with distinctive autonomic control. Methods and structure of the study. The scientific work was attended by children aged 7 and 9 years of both sexes. The initial vegetative tone (IVT) was determined by the method of variational heart rate monitoring using the automated cardiopulmonological complex REACARD, on the basis of which the children were divided into groups – sympathotonics, normotonics, vagotonics. The urgent adaptation of the sympathoadrenal system (SAS) to static stress was studied by shifting the excretion of catecholamines (СA) and DOPA in urine portions in response to a dynamometric test. Results and conclusions. Metered local static load in schoolchildren aged 7 and 9 causes changes in the functional state of the SAS, the nature of which depends on the IVT, age and gender of the children. In boys aged 7 years, sympatho- and vagotonic, isometric efforts are accompanied by unfavorable shifts, indicating the immaturity of the mechanisms of urgent adaptation of children of this age to static muscular activity. In 9-year-old boys, neurohumoral adaptive adjustments acquire a stable character, accompanied by positive, unidirectional shifts in the excretion of CA and DOPA in all IVT groups studied. Unlike girls, whose SAS reactions are more balanced at the age of 7, and at the age of 9 they are accompanied by a decrease in reserve capabilities, which is most pronounced in the state of sympathicotonia.